The incidence of orthostatic intolerance after bariatric surgery - James B. Zhang; Robyn A. Tamboli; Vance L. Albaugh; David B. Williams; Donna M. Kilkelly; Carlos G. Grijalva; Cyndya A. Shibao (Wiley, 2020)
Summary Aims Every year, over 200 000 individuals undergo bariatric surgery for the treatment of extreme obesity in the United States. Several retrospective studies describe the occurrence of orthostatic intolerance (OI) syndrome after bariatric surgery. However, the incidence of this syndrome remains unknown. Materials and methods We used a prospective, de‐identified registry of 4547 patients who have undergone bariatric surgery at Vanderbilt to identify cases of new‐onset OI. Structured chart reviews were conducted for all subjects who reported new‐onset OI post surgery. Cases of OI were confirmed using an operational case definition developed by the Vanderbilt Autonomic Dysfunction Center, and autonomic function tests results were examined for evidence of impaired autonomic function. The cumulative incidence of post‐bariatric surgery OI syndrome was estimated using a life table. Results Seven hundred forty‐one of 4547 (16.3%) patients included in our cohort reported new OI symptoms after surgery. After the chart review, we confirmed the presence of post-bariatric surgery OI syndrome in 85 patients, 14 with severe OI requiring pressor agents. At 5 years post surgery, follow‐up is reduced to 15%; the unadjusted 5‐year prevalence of OI was 1.9%. The cumulative incidence of OI syndrome adjusted for loss of follow‐up was 4.2%. Most OI cases developed during weight‐stable months (±5 kg). At the time of identification, 13% of OI cases showed evidence of impaired sympathetic vasoconstrictor activity. Conclusion OI is frequent in the bariatric population, affecting 4.2% of patients within the first 5 years postoperatively. In 13% of post-bariatric surgery OI patients, there was evidence of impaired sympathetic vasoconstriction activity.